A rapid on-site visualization platform based on RPA coupled with CRISPR-Cas12a for the detection of genetically modified papaya ‘Huanong No.1’ - Zhu, Lili; He, Gongwen; Yang, Guiqin; Yang, Wenli; He, Ying; Chen, Jian; Chen, Yanxin; Ji, Yi; Pan, Zhiwen; Yao, Juan; Chen, Xiaoyun; Jiang, Dagang (Talanta (Oxford), 2024)
The Papaya ringspot virus (PRSV)-resistant genetically modified (GM) papaya ‘Huanong No.1’ has been certified as safe for consumption and widely planted in China for about 18 years. To protect consumers' rights and facilitate government supervision and monitoring, it is necessary to establish a simple, rapid, and specific detection method for ‘Huanong No.1’. Herein, we developed a platform based on recombinase polymerase amplification (RPA) coupled with CRISPR-Cas12a for the detection of ‘Huanong No.1’. The RPA-CRISPR-Cas12a platform was found to have high specificity, with amplification signals only present in ‘Huanong No.1’. Additionally, the platform was highly sensitive, with a limit of detection (LOD) of approximately 20 copies. The detection process was fast and could be completed in less than 1 h. This novel platform enables the rapid on-site visualization detection of ‘Huanong No.1’, eliminating dependence on laboratory conditions and specialized instruments, and can serve as a technical reference for the rapid detection of other GM plants. •The RPA-CRISPR-Cas12a platform was first developed for the detection of genetically modified papaya ‘Huanong No.1’.•This novel platform enabled the on-site visualization detection of ‘Huanong No.1’, eliminating dependence on laboratory conditions and specialized instruments.•The detection process was faster than other detection methods and could be completed in less than 1 h.•The developed RPA-CRISPR-Cas12a platform showed highly specificity and sensitivity for ‘Huanong No.1’ detection.